Methods study on Hammer Garments - Marders, Joel; Salangad, Christine; Tiu, Daniel; Tupaz, Jovi Francis; Zarate, Ma. Therese Laarni (College of Engineering, 1991)
The start of second semester school year 1990-1991 introduced the group to the study of Methods Engineering. Methods Engineering as we have been taught, is concerned with the integration of the human being into a productive process. Our main intention in this, our Methods Study on Lipton Garments, is to try to incorporate those things that we have learned from our past and present Industrial Engineering subjects in order to produce a comprehensive, orderly, and feasible approach to the different problems being encountered by the plant under study. It should be placed into consideration that the results and alternatives that we will be proposing at the end of this book were entirely based on the knowledge imparted to us, as allowed by our current subjects, by our instructor and may therefore not present to be the most optimum solution. The measurements and other computations and analysis that shall be mentioned at the latter part were lifted from the different references that can be found at the end of this book.